2007
DOI: 10.1002/ijc.23139
|View full text |Cite
|
Sign up to set email alerts
|

Noggin blocks invasive growth of murine B16‐F1 melanoma cells in the optic cup of the chick embryo

Abstract: Melanoma cells originate from the neural crest and are characterized by high migratory potential and invasive growth. After transplantation into the neural tube of the chick embryo, melanoma cells spontaneously emigrate along the neural crest pathways without tumor formation or malignant growth. This emigration depends on the constitutive over-expression of bone morphogenetic protein-2 (BMP-2) and can be ablated by the BMP-antagonist noggin. When transplanted into the embryonic optic cup, melanoma cells invade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 49 publications
(48 reference statements)
2
19
0
Order By: Relevance
“…In our experiments, recombinant human Noggin protein was used as the BMP-2 blocking agent, and it was observed not to affect the high glucose-stimulated BMP-2 expression significantly, but to reduce the production of downstream Cbfα-1 and vascular calcification, correspondingly. This is consistent with the mechanisms of Noggin reported by others (Busch et al, 2008;Takayama et al, 2009). Meanwhile, our results also confirmed that high glucose-induced Cbfα-1 expression was regulated by BMP-2, and high glucose levels might induce osteoblastic differentiation and intracellular calcium deposition via the BMP-2/Cbfα-1 pathway.…”
Section: Discussionsupporting
confidence: 93%
“…In our experiments, recombinant human Noggin protein was used as the BMP-2 blocking agent, and it was observed not to affect the high glucose-stimulated BMP-2 expression significantly, but to reduce the production of downstream Cbfα-1 and vascular calcification, correspondingly. This is consistent with the mechanisms of Noggin reported by others (Busch et al, 2008;Takayama et al, 2009). Meanwhile, our results also confirmed that high glucose-induced Cbfα-1 expression was regulated by BMP-2, and high glucose levels might induce osteoblastic differentiation and intracellular calcium deposition via the BMP-2/Cbfα-1 pathway.…”
Section: Discussionsupporting
confidence: 93%
“…For embryotoxicity testing, eggs were used after 50 h of incubation (equal to stage 13 according to Hamburger and Hamilton [39]), which corresponds to approximately six human gestational weeks [40]. The eggs were prepared as described previously [41]. Resveratrol was applied in concentrations of 5, 10, 20, 50 (n = 8) and 100 µM (n = 3) on top of the blastoderm.…”
Section: Methodsmentioning
confidence: 99%
“…Melanoma cells survive, migrate and/or proliferate quite well when introduced to an inappropriate embryonic environment principally the chick eye cup. 9, 28 Kelly cells did not survive well in the eye cup environment; however, injection of cells at E6 results in the cells targeting major organs principally liver and kidney where they proliferate and form microtumours. The targeting we have observed here is distinctive to MYCN -amplified neuroblastoma cells with cells from other tumours and embryonic stem cells targeting their own distinctive locations.…”
Section: Discussionmentioning
confidence: 98%